1996
DOI: 10.1111/j.1440-1797.1996.tb00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the rehabilitation status of continuous ambulatory peritoneal dialysis and in‐centre haemodialysis in Chinese patients

Abstract: In Hong Kong, dialysis treatment has become more accessible in recent years. Due to a shortage of kidney donors patients are required to stay on dialysis for longer periods.The rehabilitation status of 181 end-stage renal failure (ESRF) patients on dialysis, 34 on in-centre haemodialysis (ICHD) and 147 on continuous ambulatory peritoneal dialysis (CAPD), at the Prince of Wales Hospital was studied. There was no statistically significant difference in physical functioning due to treatment type; however, CAPD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…A recent Canadian study of 247 nocturnal HD patients from the cohort of 1994 through 2006 showed an unadjusted 1‐year and 5‐year adverse event‐free survival of 95.2% and 80.1%, respectively 16 . Quality of life of PD and HHD has been shown to be consistently better than in‐center HD 19,20 . For the patients, the benefits include the flexibility of the treatment schedule and prescription, better dialysis adequacy, saving of travel time, and escape from inevitable frequent waiting time.…”
Section: Increased Utilization Of Home‐based Dialysis Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Canadian study of 247 nocturnal HD patients from the cohort of 1994 through 2006 showed an unadjusted 1‐year and 5‐year adverse event‐free survival of 95.2% and 80.1%, respectively 16 . Quality of life of PD and HHD has been shown to be consistently better than in‐center HD 19,20 . For the patients, the benefits include the flexibility of the treatment schedule and prescription, better dialysis adequacy, saving of travel time, and escape from inevitable frequent waiting time.…”
Section: Increased Utilization Of Home‐based Dialysis Therapymentioning
confidence: 99%
“…16 Quality of life of PD and HHD has been shown to be consistently better than in-center HD. 19,20 For the patients, the benefits include the flexibility of the treatment schedule and prescription, better dialysis adequacy, saving of travel time, and escape from inevitable frequent waiting time. In many parts of the world, nursing and nephrologist shortage is an issue.…”
Section: Increased Utilization Of Home-based Dialysis Therapymentioning
confidence: 99%
“…A recent Canadian study of 247 Nocturnal HD patients from the cohort of 1994 through 2006 showed an unadjusted 1‐ and 5‐year adverse event‐free survival of 95.2 and 80.1%, respectively 16 . Quality of life of PD and Home HD has been shown to be consistently better than In‐Centre HD 19,20 . For the patients, the benefits include the flexibility of the treatment schedule and prescription, better dialysis adequacy, saving of travel time and escape from inevitable frequent waiting time.…”
Section: Increased Utilization Of Home Based Dialysis Therapymentioning
confidence: 99%
“…16 Quality of life of PD and Home HD has been shown to be consistently better than In-Centre HD. 19,20 For the patients, the benefits include the flexibility of the treatment schedule and prescription, better dialysis adequacy, saving of travel time and escape from inevitable frequent waiting time. In many parts of the world, nursing and nephrologist shortage is an issue.…”
Section: Increased Utilization Of Home Based Dialysis Therapymentioning
confidence: 99%
“…Merkus et al (25) showed that hemodialysis patients reported lower levels of quality of life with regard to physical functioning, emotional role functioning, mental health, and pain than did PD patients. Our group also compared the rehabilitation status of patients on in-center hemodialysis (ICHD) and on CAPD (26). As compared with ICHD patients, our CAPD patients were shown to be more socially active and to have a better family life.…”
Section: Success Of Capd In Hong Kongmentioning
confidence: 99%